PENGARUH TERPAAN INFORMASI PADA PROGRAM 86 DI NET TV TERHADAP KESADARAN HUKUM MASYARAKAT KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA PEKANBARU - Hafizdzoh, Nurul; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Mass media is a media or space that can be used to publish both information and entertainment to the public. One of the many information programs presented by the media, especially television, is the reality show program. One of them is a reality show called Net 86 which was produced in collaboration between NET and the Republic of Indonesia National Police which contains cooperation between police personnel in exposing a crime. In Cultivation theory that mass media imposes attitudes and values on the audience. The purpose of this study was to determine whether there was an effect of information exposure from the